@DanielFischer We are given the definition:
For each pair of natural numbers $m \in \omega, n \in \omega$ we define the multiplication between $m,n$ (as a function $\cdot: \omega \times \omega \to \omega$) like that:
$m \cdot 0=0 \\ m \cdot n'=m \cdot n+m$
So in order to show the commutativity we have to show that $0 \cdot m=0$, $n' \cdot m=m \cdot n'$ and that $m \cdot n=n \cdot m$, right?
So in order to show that $n' \cdot m=m \cdot n'$ we show that it holds for $m=0$, then we suppose that it holds for a fixed $m, \forall n \in \omega$ and we want to show that it holds for $m'$.